Cold-water coral Atlantic thermocline ventilation records over the last 32,000 years - Elvira Beisel; Norbert Frank; Laura F Robinson; Marleen Lausecker; Ronny Friedrich; Steffen Therre; Andrea Schröder-Ritzrau; Martin Butzin (PANGAEA, 2023)
The radiocarbon analysis of uranium-thorium-dated cold-water corals (CWCs) provides an excellent opportunity for qualitative reconstruction of past ocean circulation and water mass aging. While mid-depth water mass aging has been studied in the Atlantic Ocean, the evolution of the thermocline, tightly coupled to the atmosphere, is still largely unknown. Here we present a combined 14C and 230Th/U age record obtained from thermocline dwelling CWCs with partially centennial resolution over the last 32 ka at various locations in the central and east Atlantic Ocean (Azores Front, Mauritania, Angola), as well as in the Alboran Sea.